Exploring competitive competencies for ICT/tech startup ecosystem towards the digital economy in Thailand: an empirical competency development investigation - Bhuvanij, Kriengkrai; Kasemsan, M.L.Kulthon; Praneetpolgrang, Prasong (2016)
Tech startups are seen as a new economic growth engine in Thailand which will help the country step up and produce more sophisticated high valued products and services.However, the shortage of skilled labor with innovation in knowledge-based economy has trapped Thailand in inconvenient position and losing its competitive edge. Hence in this research, the study on the competitive competencies for the tech startups were addressed by conducting in-depth interview and focus group discussion with the key stakeholders responsible for the development on the tech startups ecosystem in Thailand.The study revealed the top 5 competitive competencies classified by 1) Innovation, 2) Business Acumen and Aspiration, 3) Analytical Thinking, 4) Interpersonal Effectiveness and 5) Leadership and Result Orientation are needed most for the tech startup workforce and recommended strategy for the tech startup ecosystem in Thailand. The results of this research will help prepare ICT workforce in a larger scope to drive Thailand to be competitive in the Digital Economy and the ASEAN Community.